Delivering digital health: The barriers and facilitators to university-industry collaboration. Issue 1 (March 2021) - Austin, Daniela; May, Jon; Andrade, Jackie; Jones, Ray
Highlights: Five digital health SMEs report their expectations, experiences and barriers to success in University-Industry Collaboration. Benefits for industry included networking, raised ambitions, critical evaluation of ideas, and the technical support and expertise available from academics. Collaborations were less successful where the industrial partners had unrealistic expectations about funding and the amount of time and effort that academics could offer. For a UIC to be successful, academics need to manage expectations about what they can offer and have a review process in place from the outset of the project. Abstract: University-Industry Collaboration (UIC) is beneficial in many ways, but despite the endorsements for these collaborations, execution is challenging. To identify the benefits industrial collaborators gain from UIC, and the barriers that might prevent UICs from succeeding, this paper reports five case studies from EPIC, a project tasked with developing the digital health industry within Cornwall and the Isles of Scilly. Example cases were drawn from a set of twenty-one collaborations and included online platforms and mobile applications. The cases were selected to include the range of support provided and outcomes achieved. While the definition of success varies among UIC, those who reported successful collaboration with the university benefited from networking, raised ambitions, critical evaluation of ideas, and the technical support and expertise available from academics. Collaborations were less successful where the industrial collaborators had unrealistic expectations about funding and the amount of time and effort academics could offer. For a UIC to be successful, academics need to manage expectations about what they can offer and have a review process in place from the outset of the project.